Sistem Pendukung Keputusan Dalam Penggunaan Pestisida Untuk Tanaman Dataran Rendah - Hilda Herasmus (Jurnal Sains Informatika Terapan, 2022)
The purpose of writing this thesis is to design a decision support system in the use of computerized pesticides to make it easier for farmers to make decisions quickly, precisely and accurately as well as to process data properly. The Analytic Hierarchy Process (AHP) method is used to calculate and weight the value of pesticide use criteria. The final result obtained in the use of pesticides is the process of using pesticides which has the highest percentage of ratings based on the calculations that have been made